Aplicação do modelo Service Quality (SERVQUAL) para auferir a qualidade do serviço de uma secretaria de pós-graduação - Lisboa, Valeria da Hora Acquilino [UNIFESP] (2016)
The aim of this study was to evaluate the perception in service quality of a graduate office service from the users point of view, that is, the faculty and the student body. This study was performed at the Ophthalmology and Visual Department ? Paulista School of Medicine ? of the Universidade Federal de São Paulo. To this end, the dimensional psychometric scale Service Quality (SERVQUAL) model was adapted, which assumes that the service quality can be considered the difference between the service efficacy level and the user´s expectations. This tool is used to measure five dimensions in service quality: reliability, the capacity to provide the service with confidence and accuracy; promptness, the will to assist the users of the service and to provide results quickly; safety, the knowledge and staff´s courtesy and its ability to transmit confidence; empathy, the interest and personalized attention to the users; and tangibility, the appearance of facilities, equipments, personnel, and communication materials. Results of the study showed that the expectation of users related to the tangibility, reliability, and safety dimensions were below those expected, in contrast with the dimensions of promptness and empathy, which were equivalent to users?s expectations. No differences among sexes, age, and academic degree were related to this perception. Thus, the services offered are within users?s expectations regarding interest, attetion given and promptness of the employees and were evaluated below users?s expectations in terms of appearance of the facilities, transmission of knowledge, reliability and exactness of the services offered. Small adjustments in employee training regarding routine procedures may improve the later domains, especially as the workers were assessed as having a positive atitude towards the users of the servisse. An improvement in the appearance of the facilities, however, must be approached in a different way.